The Challenges in Developing Indonesia's Gastrodiplomacy in Jeddah - Laras Putri Olifiani; Annisatun Rahadatul Aisy (CV. Publikasi Indonesia, 2026)
As globalization continues to develop, culture and culinary traditions have become areas of great interest to the international community. In this context, several countries practice diplomacy through gastrodiplomacy as a means to introduce and promote their national culture and cuisine to the world. The Indonesia Spice Up The World gastrodiplomacy program serves as a diplomatic tool for Indonesia, a nation rich in cultural and culinary diversity, to promote its culture and cuisine globally. Although obstacles remain in its implementation, several initiatives have been carried out. The Consulate General of the Republic of Indonesia (KJRI) in Jeddah, in collaboration with the Indonesian diaspora, organizations, and other relevant agencies, continues to work toward greater integration of Indonesian gastrodiplomacy efforts in Jeddah. Important dimensions for understanding the development of Indonesian gastrodiplomacy in Jeddah include product marketing strategy, gastrodiplomacy campaigning, food event strategy, coalition-building strategy, and media relations strategy. Using an exploratory qualitative approach, this study aims to identify and explain the obstacles to the advancement of Indonesian gastrodiplomacy in Jeddah. The results of the study show that challenges persist, particularly the low participation of the restaurant diaspora. This lack of engagement hinders the optimization of culinary promotion and networking opportunities in the region.